Indústria e desenvolvimento regional: a trajetória da perfumarias Phebo em Belém - CHIACCHIO, Marcílio Alves (Universidade Federal do Pará, 2011)
The current work is the construction of a study whose area of expertise lies in the fundamentals of the history of business. Taking as a case study Perfumarias Phebo, a company of Para, which stood in the national market of perfumery. The research method consisted of gathering information regarding the location, historical background and evolution of the administrative and financial Phebo in the period 1936 to 1988, made from information provided by the company, interviews and collection of material. Soon we could perceive the trajectory of a company using the pau-rosa (Aniba rosaeodora Durke), a raw material coming from the Amazon to create your product greater market acceptance, the Soap Phebo Odor de Rosas. In the context of regional development, fragrance internalized knowledge based on the use of local raw materials and became a leader in the Brazilian market a fragrance with the expansion of its plant to the cities of Sao Paulo and Feira de Santana-Ba. In 1988 the company was sold to the group Procter & Gamble Company, American multinational. That in turn in 1998 sold the company to the Casa Granado, who now exercise control over Phebo.